Implementasi Pendidikan Karakter Cinta Damai Dalam Pembelajaran IPS Kelas V di SDN 03 Kedungwungu - Afifatul Khikmah; Jupriyanto (Cahaya Smart Nusantara, 2025)
Character education is not only about conveying values, but also about helping students understand and internalize those values through active learning, such as discussions, simulations, and value-based projects. This study aims to elaborate peace-based character education which is associated with its impact on student character building in elementary / MI. The results show, peace-loving character education helps create a safe, inclusive, and conducive learning environment for student growth and development. This has an impact on increasing learning motivation, active participation in school activities, and increasing academic achievement. The implementation of peace-loving character education has the potential to reduce the incidence of conflict, fighting, and violence in the school environment. Students become more skilled in managing conflict constructively and peacefully, creating a more harmonious atmosphere.